Fish Oil Replacement, By-Products Utilization in Aquafeeds, and Prospective Species for Mariculture Development in Sonora: A Review of Research in Aquaculture Nutrition at the University of Sonora - González-Félix, Mayra L.; Perez-Velazquez, Martin; Bringas-Alvarado, Lorena; Navarro-García, Gerardo (Facultad de Ciencias Biologicas, 2011)
Aquaculture, specifically shrimp culture, is one of the economic activities that characterize the northwest of Mexico, particularly the state of Sonora. However, the industry is currently looking for alternative species to diversify and the culture of marine fish species appears to be a promising option. Several institutions have made progress in the culture of various marine fish species, but a steady and abundant supply of fry and the availability of cost-efficient aquafeeds have kept the fish farming industry in Mexico from developing. Aquafeeds for carnivorous marine fish usually contain high levels of fish meal and fish oil, but their high prices make the use of high inclusion levels objectionable. At the Nutrition Laboratory of the Department of Scientific and Technological Research of the University of Sonora, alternative protein and oil sources are being sought and evaluated using a sustainable approach, for instance, ray fish liver oil and tilapia by-products silage. Research work with the Cortez halibut (Paralichthys aestuarius) and totoaba (Totoaba macdonaldi) has started and will continue to expand and diversify, a modest contribution to the development of fish mariculture in our state.